Design and development of a multimedia interactive lab for distance learning applications in the WWW - Kam, Y; You,, A; Chien, , S; Cheong, , S (2002)
Currently, distance education (DE) courses in Malaysia are only for the non-scientific field since DE lacks the laboratory experimentation indispensable to science. The concept of Virtual laboratory provides a timely solution. This paper describes the development and implementation of a novel, multimedia interactive laboratory (MI-LAB) for online experimentation. The aim of the MI-LAB project is to provide students access via the Internet to various experiments in conceptual physics, simplifying experimentation for home-learners and professionals in a distance teaching environment. MI-LAB's effectiveness is thoroughly demonstrated in the development of the Hall Effect experiment lab aimed at enhancing student's understanding. MI-LAB supplements the physical lab by augmenting student's learning experiences with relevant information, questions, graphs and video demonstrations. This Web approach integrates Flash actionscript to do extensive simulations and interactive animation of physics based experiments in virtual reality. MI-LAB is a low cost, zero maintenance, and risk-free alternative to conventional lab for DE.